Ipilimumab and Vemurafenib: Two Different Routes for Targeting Melanoma - Burgeiro, Ana; Mollinedo, Faustino; J. Oliveira, Paulo (Current Cancer Drug Targets, 2013)
Melanoma, a malignant tumor of melanocytes, causes the majority (75%) of all skin cancer-related deaths. The overall efficacy of different anti-cancer therapies on metastatic melanoma is quite limited, due to its high resistance to all forms of conventional treatments, including chemotherapy, radiotherapy and immunotherapy, leading to low patient survival rates. The present review identifies possible strategies for the treatment of advanced melanoma and describes two novel agents, Ipilimumab and Vemurafenib, which may now be useful for clinical practice. Ipilimumab, a humanized, IgG1 monoclonal antibody, acts through immune-modulation since it blocks cytotoxic Tlymphocyte- associated antigen-4 (CTLA-4), producing favourable antitumor immune system responses and reducing tolerance to tumor-associated antigens. Vemurafenib is a novel oral small-molecule kinase inhibitor with high selectivity and efficacy toward a specific mutated oncogenic BRAF-signalling mediator. The mechanism of action of Vemurafenib involves selective inhibition of the mutated BRAFV600E kinase that leads to reduced signalling through the aberrant MAPK pathway. However, as patients commonly develop Vemurafenib resistance, clinical trials of Vemurafenib in combination with Ipilimumab or other targeted or cytotoxic chemotherapeutic agents may provide more effective regimens with longterm clinical benefits, emphasizing the importance of simultaneously targeting several pathways. As both drugs had only modest effects on median survival, new therapeutic combinations are needed, such as BRAF inhibitors with MEK inhibitors or combinations of immunomodulators and pathway inhibitors. Such strategies should have the potential of maximizing antitumor effect while minimizing and improving clinical benefit. Nevertheless, these two new agents open a promising view into an effective management of melanoma.
Keywords: Vemurafenib